Financial Management as the Foundation of Organizational Stability and Sustainability - Anita Ardiyanti (ProBisnis : Jurnal Manajemen, 2026)
Financial management plays a fundamental role in ensuring organizational stability and long-term sustainability. Effective financial management enables organizations to plan, allocate, and control financial resources efficiently while responding to dynamic economic and institutional challenges. This study examines how financial management functions—including financial planning, budgeting, financial reporting, and internal control—contribute to organizational stability and sustainability. Through a conceptual and analytical approach, the study highlights that sound financial management supports informed decision-making, enhances accountability, and mitigates financial risks. Furthermore, transparent and accountable financial practices strengthen stakeholder trust and support sustainable organizational growth. The findings suggest that organizations with strong financial management systems are better positioned to maintain financial resilience, achieve strategic objectives, and ensure long-term sustainability in an increasingly complex and competitive environment.